1988
DOI: 10.1002/lsm.1900080304
|View full text |Cite
|
Sign up to set email alerts
|

Partial nephrectomy using the Nd:YAG Laser: A comparison of the 1.06 μ and 1.32 μ lasers employing different delivery systems

Abstract: A comparative study of the 1.06 mu and the 1.32 mu Nd:YAG laser using a variety of delivery systems (focusing handpiece, freehand GI quartz fiber, or frosted laser scalpel) was undertaken to determine the usefulness of these modalities in performing partial nephrectomies in dogs. Variables evaluated included total operative time, total joules expended, estimated amount of blood loss, and extent of renal tissue damage. The contact laser scalpel provided the greatest precision and speed, but no hemostasis, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…After use of monopolar electrocautery, the initial thermal lesion of 75 to 500 mm can increase as much as threefold by 6 weeks. 24 The necrotic margin for the diode laser in our study increased from approximately 0.05 cm in the acute kidneys to 0.3 to 0.5 cm in the 2-week survival kidneys.…”
Section: Discussionmentioning
confidence: 96%
“…After use of monopolar electrocautery, the initial thermal lesion of 75 to 500 mm can increase as much as threefold by 6 weeks. 24 The necrotic margin for the diode laser in our study increased from approximately 0.05 cm in the acute kidneys to 0.3 to 0.5 cm in the 2-week survival kidneys.…”
Section: Discussionmentioning
confidence: 96%
“…Landau et al (1987) used a contact Nd:YAG laser with a cone-shaped tip and reported 2.7 mm as the maximal depth of tissue destruction. Johnson et al (1988) used a variety of delivery systems with the Nd : YAG laser in partial nephrectomy in dogs and found maximal acute renal damage up to 1.8 mm. With the frosted tips a portion of the energy is scattered diffusely from the roughened lateral sides of the probe, allowing better coagulating properties (Foster et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…34; however, the transected collecting systems did not seal and would have required closure. Although the operating time for polar nephrectomy was longer using the Ho:YAG laser than using the Nd:YAG laser and the GI-free fiber at either 59 or 83 W (4-7 minutes), the total J was considerably lower than the 14,136-18,067 J required with the Nd: YAG laser [7].…”
Section: Imentsmentioning
confidence: 94%